Impact of Vancomycin‐Induced Changes in the Intestinal Microbiota on the Pharmacokinetics of Simvastatin - Jung Sunwoo; Sang Chun Ji; Andrew HyoungJin Kim; Kyung‐Sang Yu; Joo‐Youn Cho; In‐Jin Jang; SeungHwan Lee (Wiley, 2020)
The pharmacokinetic (PK) properties of drugs are affected in several ways by interactions with microbiota. The aim of this study was to investigate the effects of oral vancomycin on the gut microbiota and, consequently, on the PKs of simvastatin. An open‐label, single arm, sequential crossover study was conducted in six healthy Korean male subjects. After 6 days on a control diet, simvastatin 40 mg was orally administered to the subjects before and after 1 week of oral vancomycin treatment. Blood samples for PK analysis and fecal samples for metagenomic and metabolomic analyses were collected. After vancomycin treatment, the richness of microbiota considerably decreased, and the composition was altered. In particular, the relative abundance of Bacteroidetes decreased, whereas that of proteobacteria increased. In addition, changes in fecal metabolites, including D‐glucuronic acid, were observed. However, systemic exposure of simvastatin was not changed whereas that of hydroxysimvastatin showed a tendency to increase. The relationship between the change of PKs of simvastatin and the change of gut microbiota and fecal metabolites were not clearly observed.